Measuring Level of Depression, Anxiety and Stress in Nursing Students with Web-Based Expert System - Niken Sukesi; Wahyuningsih Wahyuningsih (GLOBAL HEALTH SCIENCE GROUP, 2022)
The development of information technology in the era of 5.0 which is increasingly rapidly demands the readiness to usecomputers in various fields, especially nursing. Nursing as .part of the health sciences in the face of the industrial era seeks to synergize in the provisionof nursing services by using the application of information technology to assist the service process by using an expert system. Expert system is an information system that contains the knowledge of one or more related human experts a specific area of knowledge. This expert system to help diagnose as well as the prevention and treatment of a disease. This expert system is used to assess the level of depression, anxiety and stress in nursing students. Assessment of the level of depression, anxiety and stress using DASS 42 (Depression Anxiety Stress Scale 42). This questionnaire is standard so it does not need to be tested. This expert system uses web and android-based linear regression methods. The purpose of this expert system is to help someone self-diagnose aspects of the level of depression, anxiety and stress suffered based on the symptoms they experience. The research method used is the literature study method, namely by obtaining data from application program books, journals on expert systems, other sources on the internet. Generates the output aspect of the selected symptom. This website application has been uploaded to the internet with the url address http://dass.uwhs.ac.id/ and android application https://files.appsgeyser.com/System%20DASS%2042_15411297.apk?utm_source=event_ema il&utm_medium=email&utm_campaign=download_your_app.